Pengaruh Discovery Learning Berbantu Papan Pintar Perkalian terhadap Hasil Belajar Matematika Siswa Kelas III: The Effect of Discovery Learning Assisted by a Multiplication Smart Board on the Mathematics Learning Outcomes of Third-Grade Students - Sriwahyuni Hattab; Sarintan N Kaharu; Nurul Kamisani; Zulnuraini Zulnuraini; Eva Setya Rini (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to determine the effect of the Discovery Learning model, supported by a multiplication "smart board" aid, on the mathematics learning outcomes of third-grade students at SD 24 Palu. The study was motivated by students' poor understanding of multiplication concepts—evidenced by difficulties in solving multiplication problems accurately—and the suboptimal use of concrete, engaging, and interactive learning media during instruction. These conditions resulted in mathematics learning outcomes falling short of expected levels. A quantitative approach with a quasi-experimental design was employed. The research subjects comprised all third-grade students at SD 24 Palu, divided into experimental and control groups. The research instrument was a learning achievement test that had undergone validity and reliability testing, ensuring its suitability for data collection. Data analysis involved normality tests, homogeneity tests, Normalized Gain (N-Gain) analysis, and independent sample t-tests using SPSS version 31. The results indicate a significant effect of the Discovery Learning model—supported by the multiplication smart board—on students' mathematics learning outcomes. This is evidenced by a t-test significance value of less than 0.05 and an improvement in learning outcomes in the experimental class falling into the "medium" category based on N-Gain analysis. Thus, the Discovery Learning model supported by the multiplication smart board is proven effective in enhancing mathematics learning outcomes for elementary school students, particularly regarding the topic of whole-number multiplication.